The BEACH Domain Is Critical for Blue Cheese Function in a Spatial and Epistatic Autophagy Hierarchy - Sim, Joan; Osborne, Kathleen A.; Argudo García, Irene; Matysik, Artur S.; Kraut, Rachel (Frontiers in Cell and Developmental Biology, 2019)
Drosophila blue cheese (bchs) encodes a BEACH domain adaptor protein that, like its human homolog ALFY, promotes clearance of aggregated proteins through its interaction with Atg5 and p62. bchs mutations lead to age-dependent accumulation of ubiquitinated inclusions and progressive neurodegeneration in the fly brain, but neither the influence of autophagy on bchs-related degeneration, nor bchs’ placement in the autophagic hierarchy have been shown. We present epistatic evidence in a well-defined larval motor neuron paradigm that in bchs mutants, synaptic accumulation of ubiquitinated aggregates and neuronal death can be rescued by pharmacologically amplifying autophagic initiation. Further, pharmacological rescue requires at least one intact BEACH-containing isoform of the two identified in this study. Genetically augmenting a late step in autophagy, however, rescues even a strong mutation which retains only a third, non-BEACH containing isoform. Using living primary larval brain neurons, we elucidate the primary defect in bchs to be an excess of early autophagic compartments and a deficit in mature compartments. Conversely, rescuing the mutants by full-length Bchs over-expression induces mature compartment proliferation and rescues neuronal death. Surprisingly, only the longest Bchs isoform colocalizes well with autophagosomes, and shuttles between different vesicular locations depending on the type of autophagic impetus applied. Our results are consistent with Bchs promoting autophagic maturation, and the BEACH domain being required for this function. HIGHLIGHTS The autophagic adaptor blue cheese is placed in an epistatic hierarchy, using pharmacological and genetic modulation of bchs- motor neuron degeneration. An intact BEACH isoform can promote autophagic proliferation, and in primary larval brain neurons Bchs shuttles to different components of the autophagy machinery, dependent on the stimulus.